Assessment of quality of life (QoL) of burn patients in India using BSHS-RBA scale. Issue 3 (May 2016) - Ahuja, Rajeev B.; Mulay, Amit M.; Ahuja, Aarti
Highlights: Aim: Identify prognostic variables affecting Qol of burn patients. BSHS-RBA scale in Hindi language was used. Factors associated with poor QoL were identified. Psychological counseling, work rehabilitation and control of itch are recommended. Abstract: Introduction: The Burn Specific Health Scale-Brief (BSHS-B) is a popular instrument to measure quality of life (QoL) in burn patients. The current study aims at identifying the prognostic variables for our burn population using the BSHS-RBA (revised, brief and adapted) scale. Materials and methods: The study was conducted on 60 post-burn patients using the BSHS-RBA scale. The questionnaire was administered by an interview as majority of patients were illiterate. The socio-demographic and clinical variables were analyzed against domain scores and total scores of the scale, using Mann-Whitney test and Kruskal Wallis test. Results: The median age of the sample was 28 years, of which 60% were females. Their median TBSA burn was 30%. The median time since burn at the time of interview was 10 months. Higher scores were noted in the domains of simple abilities and mobility, hand function and interpersonal relationship, while poorer scores were recorded in domains of skin sensitivity and body image. Discussion: The mean score in our study was 2.36, which is quite less as compared to reports from high income countries (range: 2.58–3.36). This study provides an insight on an aspect of burn care outcome, which can be reasonably expected in low income countries with the available standard of care. Being a female, presence of hand and face burn, requirement of corrective surgeries and inability to resume work were factors associated with poor QoL. Conclusion: Strategies to improve QoL of burn patients should target psychological aspects, work rehabilitation (early release of contractures) and skin hypersensitivity (including itching) to derive maximum benefit.